A new distribution of Myrrophis dakkrongensis Nguyen, Le, Lathrop, Vo, Murphy, 2024 (Squamata: Serpentes: Homalopsidae) in Lam Dong province, Vietnam - Hong Phuc, Chau; Phan Vu Phuc Lan,; Ngoc Duong, Pham; Thi Phuong Thao, Nguyen; Dang Hoang Vu, Nguyen (Journal of Forestry Science and Technology, 2025)
The newly described species, Myrrophis dakkrongensis Nguyen, Le, Lathrop, Vo, Murphy, 2024, was discovered in rubber plantations and wetland areas within forests in the Dak Krong River Basin in Dak Glong district, Dak Nong province, Vietnam. It was thought to be endemic to that area. In this study, we expand the species’ distribution by providing a new record based on field surveys in a different area, the Dong Nai River Basin in Lam Dong province, Vietnam. The new record is also from a new habitat type, a stream flowing through a forest. For conservation purposes, data collection and morphological identification were conducted using the Capture-Analyze-Release approach (CAR). Details regarding the new habitat type (the stream), other field metadata, and the voucher photos are available on iNaturalist (https://www.inaturalist.org/observations/238896488). Morphological characteristics of the juvenile specimen match the original description of M. dakkrongensis but have some different characteristics from adult specimens in type series as tail length/total length ratio = 0.22 (vs. 0.14 – 0.16) and subcaudals 43 (vs 34 – 42). The coloration of the new record mostly matches the original descriptions, but it is slightly lighter. Further research on the species’ overall distribution in surrounding river basins such as the Vam Co River and the Ba River; habitat types; and geographical phylogeny are necessary to enhance our understanding of this species.